Dynamic interdependence of the Indonesian Rupiah with the ASEAN and the world largest Forex markets - M. Shabri Abd. Majid; Hizir Sofyan; Moh. Rizky Rahmanda (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study empirically investigates the dynamic interdependencies of the Indonesian Rupiah (IDR) with the ASEAN, European, and Japanese forex markets. Using daily nominal exchange rates of Indonesia, Thailand, Malaysia, Singapore, the Philippines, Europe, and Japan spanning from January 1, 2008 to December 31, 2015, the study employs the impulse response functions and variance decomposition analysis based on the vector autoregression method. The study documented that the IDR more responded to innovations in the forex market of Singapore as compared to other ASEAN forex markets. Additionally, the ASEAN forex markets were more interdependence with the forex markets of Japan rather than Europe. Since the forex markets become more interdependent both regionally and internationally, thus it needs for policy coordination among the countries to mitigate the impact of forex fluctuations if these countries are to grasp the benefits of greater forex markets’ interdependence.